Stunned Myocardium Syndrome Following Severe Traumatic Brain Injury with Multisystem Complications: A Neurocritical Care Challenge - Mishra, Bipin K.; Mudgal, Kavi; Agrawal, Deepak (Indian Journal of Neurotrauma, 2025)
Stunned myocardium syndrome (SMS) is a reversible myocardial dysfunction occurring after ischemia and reperfusion, commonly described in cardiac contexts but underrecognized in traumatic brain injury (TBI). We present a case of severe TBI complicated by SMS after cardiac arrest, underscoring the importance of early recognition and multidisciplinary management.
Keywords: neurocritical care; severe traumatic brain injury; SMS; stunned myocardium syndrome